2007
DOI: 10.1111/j.1551-2916.2007.01517.x
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Properties of Ternary Ti3AlC2 and its Composites from Ti–Al–C Powder Mixtures With Ceramic Particulates

Abstract: A layered ternary carbide phase, Ti3AlC2, was synthesized by hot pressing from the starting materials of Ti, aluminum, and activated carbon at 1400°C for 2 h. Its composites were also fabricated through addition of micro‐sized SiC and partially stabilized zirconia particulates to the pulverized Ti3AlC2 powders. The polycrystalline Ti3AlC2 ceramic obtained has a flexural strength of 172 MPa and a fracture toughness of 4.6 MPa·m1/2, respectively. This compound is relatively soft (Vikers hardness of 2.7 GPa) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…In fact, Ti 3 AlC 2 has been found to be carbon deficient with respect to its ideal stoichiometry in the previous work, 40 and the influence of carbon content on the preparation of Ti 3 AlC 2 by using the conventional methods has also been investigated. 9,41,42 Figure 2 shows the current-time curve of the electroreduction process of the 3TiO 2 /0.5Al 2 O 3 /1.5C precursor. As shown in the figure, the current variation can be divided into two stages, i.e., the rapid decline and the slow decline.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, Ti 3 AlC 2 has been found to be carbon deficient with respect to its ideal stoichiometry in the previous work, 40 and the influence of carbon content on the preparation of Ti 3 AlC 2 by using the conventional methods has also been investigated. 9,41,42 Figure 2 shows the current-time curve of the electroreduction process of the 3TiO 2 /0.5Al 2 O 3 /1.5C precursor. As shown in the figure, the current variation can be divided into two stages, i.e., the rapid decline and the slow decline.…”
Section: Resultsmentioning
confidence: 99%
“…can be used to prepare Ti 3 AlC 2 from pure metals (Ti/Al/C), carbides (TiC x /Al or Ti/Al 4 C 3 /TiC), and hydride (TiH 2 /Al/C). 4,[9][10][11][12][13][14][15][16][17] However, these processes are commonly performed under severe conditions, such as high temperature and high pressure. Furthermore, the conventional production of pure metals (such as Ti) usually suffers from the energy-intensive and tedious process.…”
mentioning
confidence: 99%
“…Transformation toughening in MAX phases can be traced back to 2007 [ 37 , 38 ]. A 20 wt % ZrO 2 /Ti 3 AlC 2 was obtained by uniaxial hot-pressing at 1450 °C under a pressure of 20 MPa for 2 h in vacuum and the measured fracture toughness of 20 wt % ZrO 2 /Ti 3 AlC 2 composite was 6.8 MPa·m 1/2 , while the fracture toughness of monolithic Ti 3 AlC 2 was 4.6 MPa·m 1/2 [ 37 ].…”
Section: Toughening In Nanolayered Max Phasesmentioning
confidence: 99%
“…Transformation toughening in MAX phases can be traced back to 2007 [ 37 , 38 ]. A 20 wt % ZrO 2 /Ti 3 AlC 2 was obtained by uniaxial hot-pressing at 1450 °C under a pressure of 20 MPa for 2 h in vacuum and the measured fracture toughness of 20 wt % ZrO 2 /Ti 3 AlC 2 composite was 6.8 MPa·m 1/2 , while the fracture toughness of monolithic Ti 3 AlC 2 was 4.6 MPa·m 1/2 [ 37 ]. The SEM observations of the fracture surface indicated that the fracture toughness improvement can be ascribed to the compressive stress in the matrix generated by the ZrO 2 particles transformation process.…”
Section: Toughening In Nanolayered Max Phasesmentioning
confidence: 99%
“…Second phase particles, such as Al 2 O 3 , TiB 2 , and SiC reinforcing particles have been incorporated to strengthen the Ti 3 AlC 2 matrix . As the Al 2 O 3 and SiC particles did not react with the Ti 3 AlC 2 matrix during composite processing, the interfaces are weak and only limited strengthening can be achieved.…”
Section: Introductionmentioning
confidence: 99%